2018
DOI: 10.1002/jcp.26415
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype‐based association of two SNPs in miR‐323b with unexplained recurrent spontaneous abortion in a Chinese Han population

Abstract: Single nucleotide polymorphisms (SNPs) in miRNAs are associated with the risk to development of certain human diseases and affect the regulatory capacity of miRNAs. However, the relationship between miRNAs polymorphisms and recurrent pregnancy loss (RPL) is still largely unknown. Our study found that one SNP rs56103835 T>C in miR-323b coding region was associated with the increase risk of human unexplained RPL (URPL), but no differences were found in another SNP rs75330474 C>T. However, in two-locus haplotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…RSA is a common pregnancy complication affecting 1-3% of couples trying to conceive. Studies have shown that miRNAs may play an important role in URSA and SNPs located both in the pre-miRNAs or within miRNA-binding sites are likely to influence the expression and function of the miRNA target and thus may contribute to susceptibility to URSA ( 28-30 ). The most common and widely studied SNPs in miRNAs are miR-146a rs2910164, miR-196a2 rs11614913 and miR499a rs3746444.…”
Section: Discussionmentioning
confidence: 99%
“…RSA is a common pregnancy complication affecting 1-3% of couples trying to conceive. Studies have shown that miRNAs may play an important role in URSA and SNPs located both in the pre-miRNAs or within miRNA-binding sites are likely to influence the expression and function of the miRNA target and thus may contribute to susceptibility to URSA ( 28-30 ). The most common and widely studied SNPs in miRNAs are miR-146a rs2910164, miR-196a2 rs11614913 and miR499a rs3746444.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Lim et al 7 showed that the level of IL-6 in the decidual tissue of URSA patients was low, which was inconsistent with our study. This might be because there were differences in environment between different countries, ethnic groups, or regions, and studies have proved that URSA may be related to gene polymorphism 8 ; or it might be that IL-6 was a proinflammatory factor, which further damaged trophoblast cells and did harm to embryonic development. Some experiments 9,10 found that the content of IL-6 and related mRNA in the decidual tissues of URSA patients increased, which was consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Additional findings revealed the involvement of miR‐326 in intrauterine adhesion, leading to infertility and pregnancy loss, here it was deciphered that the said miRNA negatively regulates the TGF‐β1/Smad3 pathway by targeting TGF‐β1, suggesting its vital role as a prognostic marker and as a therapeutic target (Ning et al, 2018). Furthermore, structural changes, such as nucleotide polymorphisms in miRNAs, can also lead to pregnancy loss by modulating target selection that impacts pregnancy outcomes influencing proliferation, invasion, migration, and embryonic development pathways (Jeon et al, 2012; Lee et al, 2020; X. Q. Wang, Li, et al, 2018). However, only a handful of studies have shown dysregulated expression of lncRNAs responsible for URPL by altering numerous biological pathways, among which the majority are inflammatory and infection pathways genes (Z. Huang, Du, et al, 2018; Wang et al, 2014).…”
Section: Ncrnas In Women's Healthmentioning
confidence: 99%